KONTROVERSI STRICT LIABILITY DALAM HUKUM PERLINDUNGAN KONSUMEN - Gunawan, Johannes (Faculty of Law, Parahyangan Catholic University, 2018)
This paper, using a comparative law method, discusses the controversy concerning the meaning and interpretation of strict liability as found in the Indonesian Consumer Protection Law. How in Indonesia this concept is understood will be compared to how the same concept (strict liability) is developed within the Dutch civil law system and the common law system (especially in the United Kingdom(UK)and United State of America (USA)). A brief description of the meaning and development of the concept in Indonesia will be given, including the historical trajectory of the concept within those different systems and the important case laws in the Netherlands, UK and USA. All this will provide a background for the author to discuss and criticize the strict liability concept as found regulated in Law No. 8 of 199 on Consumer Protection.